2001
DOI: 10.1103/physrevlett.86.1562
|View full text |Cite
|
Sign up to set email alerts
|

Nothing Moves a Surface: Vacancy Mediated Surface Diffusion

Abstract: We report scanning tunneling microscopy observations, which imply that all atoms in a Cu(001) surface move frequently, even at room temperature. Using a low density of embedded indium "tracer" atoms, we visualize the diffusive motion of surface atoms. Surprisingly, the indium atoms seem to make concerted, long jumps. Responsible for this motion is an ultralow density of surface vacancies, diffusing rapidly within the surface. This interpretation is supported by a detailed analysis of the displacement distribut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
112
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(129 citation statements)
references
References 12 publications
7
112
0
Order By: Relevance
“…We have used first-principles densityfunctional theory to calculate E f and E m for vacancies and adatoms on the pure Cu surface. Our results, consistent with other previous reports 3,4, [16][17][18] , show that island ripening on the pure Cu surface is mediated by surface vacancies. In order to understand the slowing effect of Pd in the limit of dilute alloys ( < ∼ 0.20 ML Pd), we have explored the interaction of vacancies with isolated buried Pd atoms.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We have used first-principles densityfunctional theory to calculate E f and E m for vacancies and adatoms on the pure Cu surface. Our results, consistent with other previous reports 3,4, [16][17][18] , show that island ripening on the pure Cu surface is mediated by surface vacancies. In order to understand the slowing effect of Pd in the limit of dilute alloys ( < ∼ 0.20 ML Pd), we have explored the interaction of vacancies with isolated buried Pd atoms.…”
Section: Discussionsupporting
confidence: 83%
“…In this work, we use Cu-adatom island-ripening measurements to show that Cu(001) surface diffusion is slowed by the presence of buried Pd atoms near the surface. Previous studies 3,4, [16][17][18] found that Cu(001) surface diffusion is mediated by surface vacancies, and we propose that the alloy slows surface diffusion by increasing the energetic barrier to vacancy diffusion. Using first-principles density-functional theory calculations, we find that Cu surface vacancies are attracted to buried Pd atoms, which inhibits vacancy migration on alloyed terraces.…”
Section: Introductionmentioning
confidence: 99%
“…The freezing of i=4 processes marks a violation of detailed balance (since such a vacancy, if it existed, could be filled by a roving adatom); however, given the negligible occurrence of such vacancies in our simulations, the violation should be insignificant. In some physical systems, motion of surface vacancies does evidently dominate mass transport [21]. Again, our goal in these calculations is not to account generally for experiments but to create a fully-controlled data set to see how well the dynamics can be described using our Fokker-Planck formalism.…”
Section: Modelmentioning
confidence: 99%
“…Vacancy attachment has an additional barrier compared with vacancy diffusion because it requires the concerted motion of two atoms. Vacancy motion has been confirmed for this system by tracing the displacement of substitutional In atoms on Cu(100) [246,247]. The experiments for Ag/Ag(111) have been repeated for adatom and vacancy islands placed within a big vacancy island (Figure 20.20c,d) [112].…”
Section: The Ostwald Ripeningmentioning
confidence: 99%